Acoustic analysis of the alarm call of the Anatolian ground squirrel Spermophilus xanthoprymnus: a description and comparison with alarm calls of the Taurus S. taurensis and European S. citellus ground squirrels - Schneiderová, Irena; Policht, Richard (Die Naturwissenschaften, 2012)
The Anatolian ground squirrel Spermophilus xanthoprymnus like other ground-dwelling sciurids, emits alarm calls in the presence of predators. In this study, we provide a description of the acoustic structure of alarm call of this species and compare it to those of two closely related species, the Taurus ground squirrel Spermophilus taurensis and the European ground squirrel Spermophilus citellus. The alarm call of S. xanthoprymnus is a tonal sound mostly consisting of two different elements-the first element has low frequency modulation while the second element is highly frequency modulated. A similar basic structure can be found in the alarm calls of some other old world ground squirrel species of the genus Spermophilus, including S. taurensis and S. citellus. Despite this similarity, we found that these three species can be clearly distinguished on the basis of their alarm calls. Differences in the acoustic structure of S. xanthoprymnus and S. taurensis calls are especially remarkable, as these two species were considered to be conspecific until 2007. S. xanthoprymnus and S. taurensis were also demonstrated to have closer acoustic similarity, which is in contrast to results based on molecular data indicating that S. taurensis is most closely related to S. citellus.
Keywords: druhová specificita; Animals; shluková analýza; Female; mužské pohlaví; zvířata; Cluster Analysis; Male; akustika; vokalizace zvířat; Acoustics; Species Specificity; Sciuridae; Vocalization, Animal; ženské pohlaví